An Exact Algorithm for the Hazardous Orienteering Problem - Montemanni, Roberto; Smith, Derek H. (Networks, 2025)
ABSTRACT The hazardous orienteering problem is the topic of this study. It is a variant of the well‐studied orienteering problem, where a vehicle, given a maximum mission time, has to select and visit customers out of a set of requests, aiming at maximizing the total profit associated with the customers selected. In the hazardous version of the problem we consider, the customers are associated with parcels that have to be collected, and some of them might explode during the transportation, after having been picked up. The probability of explosion depends on the characteristics of the parcel and on the time spent by the dangerous parcel itself on the vehicle. If an explosion happens, the collected profit is totally lost. The target becomes then to select the tour that maximizes the expected profit, taking into account the probability of catastrophic events happening. In this article, we propose an exact solving approach based on a mixed integer linear programming model which is dynamically modified by adding new constraints. The computational results substantially improve the state‐of‐the‐art for the problem.